PL and HCI: Better Together. - CHASINS, SARAH E.; GLASSMAN, ELENA L.; SUNSHINE, JOSHUA (Communications of the ACM, 2021)
The article calls for the combination of human-computer interaction with programming languages. Examples of the alleged utility and benefits of combining the two fields are offered, the combination is contrasted with other fields dealing with human-centered aspects of programming languages including software engineering, the psychology of programming, and computer science education, and alleged misconceptions about programming languages and human-computer interaction are outlined.